Simulation of the process of water purification in multilayered micro porous media - Prysiazhniuk, Olena; Safonyk, Andrii; Terebus, Anna (Моделювання, керування та інформаційні технології, 2019)
The mathematical model of the process of adsorption purification of water from impurities in multilayer microporous filters is formulated. An algorithm for numerically-asymptotic approximation of solution of the corresponding nonlinear singularly perturbed boundary value problem is developed. The developed model allows to investigate the distribution of concentration of pollutant inside the filer.